2014
DOI: 10.1016/j.bpj.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Conformational State Distributions and Catalytically Relevant Dynamics of a Hinge-Bending Enzyme Studied by Single-Molecule FRET and a Coarse-Grained Simulation

Abstract: Over the last few decades, a view has emerged showing that multidomain enzymes are biological machines evolved to harness stochastic kicks of solvent particles into highly directional functional motions. These intrinsic motions are structurally encoded, and Nature makes use of them to catalyze chemical reactions by means of ligand-induced conformational changes and states redistribution. Such mechanisms align reactive groups for efficient chemistry and stabilize conformers most proficient for catalysis. By com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 71 publications
1
29
2
Order By: Relevance
“…The data for FGFR1 KD (Figs 1b and 5a–c) are in sharp contrast with recent observations obtained for a metabolic phosphoglycerate kinase (PGK)40. MD simulations and smFRET show equilibrium between two populations (“expanded” and “compact”) for ligand-free PGK; substrate binding only slightly shifts the equilibrium toward the compact state.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The data for FGFR1 KD (Figs 1b and 5a–c) are in sharp contrast with recent observations obtained for a metabolic phosphoglycerate kinase (PGK)40. MD simulations and smFRET show equilibrium between two populations (“expanded” and “compact”) for ligand-free PGK; substrate binding only slightly shifts the equilibrium toward the compact state.…”
Section: Discussioncontrasting
confidence: 95%
“…Furthermore, we have also addressed a major obstacle of non-disruptive labeling of target regions that are key for the activation process, and therefore functionally sensitive, by applying the genetically encoded, site-specific incorporation of unnatural amino acids (UAAs), coupled with rapid and highly specific labeling with a chemical reporter33343536373839. Importantly, using this novel type of FRET-based construct, combined with MD simulations, we show that FGFR1 KD displays switch-like activation owing to a high free energy barrier between its non-phosphorylated and phosphorylated states, contrasting some recent examples for other kinases supporting preexisting equilibrium242640.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…This entropic model is consistent with the recent observation of a highly dynamic population of the intermediate closed/open state in the LBD of mGluR3 in solution . Data from structurally related model proteins, such as maltose‐binding protein and phosphoglycerate kinase have also revealed large‐amplitude oscillations around the hinge axis in the unliganded state whose amplitude is reduced upon either ligand binding or mutations that rigidify the hinge. However, it is also possible that the closed/open dimer in mGluR1 LBD is favored over the open–open one enthalpically.…”
Section: Discussionsupporting
confidence: 88%
“…This highly versatile protein adopts a variety of conformations while binding its substrates, and these are simply those sampled along one or two principal directions of motions accessible to the unbound ubiquitin, also seen by NMR residual dipolar coupling. A more recent example is the single-molecule Förster resonance energy transfer analysis of phosphoglycerate kinase (PGK) dynamics by Fitter and coworkers [23••]. In that study, Fitter and coworkers elegantly showed that (i) the experimentally detected functional (hinge-bending) motions of the enzyme are encoded by the fold, as predicted by ENMs, and (ii) those motions are already performed in the ligand-free state of PGK domains, prior to substrate-binding.…”
Section: Introductionmentioning
confidence: 99%